A round peg in a square hole: strategy-situation fit of intra- and interpersonal emotion regulation strategies and controllability. Issue 5 (3rd July 2020) - Wenzel, Mario; Rowland, Zarah; Weber, Hannelore; Kubiak, Thomas
ABSTRACT: Although the importance of contextual factors is often recognised, research on emotion regulation strategies (ERS) has mainly focused so far on the effectiveness of ERS across situations. In the present research, we tested the strategy-situation fit hypothesis, which does not assume general effectiveness of ERS but instead stresses the importance of the congruency between ERS and the contexts in which they are used. Using a longitudinal Ambulatory Assessment dataset ( N  = 138), we found that controllability of a situation positively moderated the effectiveness of interpersonal ERS, such that, e.g. providing feedback to others was significantly associated with less positive feelings but only in less controllable situations. Intrapersonal ERS were negatively moderated by controllability, such that downplaying a negative situation was associated with less negative feelings in less controllable situations. Finally, favouring interpersonal over intrapersonal ERS was also positively moderated by controllability, demonstrating the situational fit of ERS in daily life.